I need to prove that knowing the binormal vector $\vec{b}(s)$ of a regular curve $\alpha$ parametrized by arc length is sufficient to know $|\tau(s)|$ and $\kappa(s)$, respectively the module of torsion and the curvature of $\alpha$.

By the third Frenet Formula, $|\vec{b}'|=|\tau|\, ||\vec{n}||=|\tau|$. No problems here to determine $|\tau|$.

I'm working now in a way to determine $\kappa$. What I did was that:

$$\vec{b}=\vec{t}\wedge\vec{n}=\frac{1}{\kappa}(\vec{n}+\tau \vec{b})\wedge \vec{n}=\frac{1}{\kappa}(\vec{n}\wedge\vec{n})+\frac{\tau}{\kappa}(\vec{b}\wedge \vec{n})=\frac{\tau}{\kappa}(\vec{b}\wedge\vec{n}) $$

Am I on the right way? What can I do?

  • 2
    $\begingroup$ That formula you used for $t$ is not correct. It implies $|\tau| = |\kappa|$ by taking the norm of the last step, which is certainly not true. Instead take the second derivative of $b$. $\endgroup$ Sep 6 '19 at 19:46
  • $\begingroup$ @NinadMunshi why is not correct? By the second Frenet formula, $$n'=-\kappa t-\tau b\implies n'+\tau b=-\kappa \tau\implies t=\frac{-n'-\tau b}{\kappa}$$ So, i just did a mistake on the signal $\endgroup$ Sep 7 '19 at 0:01

We are given $B(s)$ for the arc-length parametrized curve $\alpha(s)$; we wish to find $\vert \tau(s) \vert$ and $\kappa(s)$.

As pointed out by our OP Mateus Rocha in the text of the question itself, $\vert \tau(s) \vert$ is easily had; we simply exploit the Frenet-Serret equation

$\dot B(s) = -\tau(s) N(s) \tag 1$

to write

$\vert \tau(s) \vert = \vert \tau(s) \vert \vert N(s) \vert = \vert \tau(s) N(s) \vert = \vert \dot B \vert, \tag 2$


$\vert \tau(s) \vert = \vert \dot B(s) \vert, \tag 3$

giving us $\vert \tau(s) \vert$; we used

$\vert N(s) \vert =1 \tag 4$

in deriving (2); next, we differentiate (1):

$\ddot B(s) = -\dot \tau(s) N(s) - \tau(s) \dot N(s)$ $= -\dot \tau(s) N(s) - \tau(s) (-\kappa(s) T(s) + \tau(s) B(s)) = -\dot \tau(s) N(s) + \tau(s) \kappa T(s) - \tau^2(s) B(s), \tag 5$

where we have exploited the Frenet-Serret formula

$\dot N(s) = -\kappa(s) T(s) + \tau(s) B(s); \tag 6$

from (1),

$\dot \tau(s) \dot B(s) = -\tau(s) \dot \tau N(s); \tag 7$

from (5),

$\tau(s) \ddot B(s) = -\tau(s) \dot \tau(s) N(s) + \tau^2(s) \kappa(s) T(s) - \tau^3(s) B(s); \tag 8$

thus, subtracting (7) from (8),

$\tau(s) \ddot B(s) - \dot \tau(s) \dot B(s) = \tau^2(s) \kappa T(s) - \tau^3(s) B(s), \tag 9$


$\tau^2(s) \kappa(s) T(s) = \dot \tau(s) \dot B(s) - \tau(s) \ddot B(s) + \tau^3(s) B(s); \tag{10}$

this yields

$\tau^2(s) \kappa(s) = \tau^2(s) \kappa(s) \vert T(s) \vert = \vert \tau^2(s) \kappa(s) T(s) \vert = \vert \dot \tau(s) \dot B(s) - \tau(s) \ddot B(s) + \tau^3(s) B(s) \vert, \tag{11}$


$\vert T(s) \vert = 1; \tag{12}$

a minor re-arrangement results in

$\kappa(s) = \dfrac{\vert \dot \tau(s) \dot B(s) - \tau(s) \ddot B(s) + \tau^3(s) B(s) \vert}{\tau^2(s)}. \tag{13}$

Nota Bene: We observe that (13) is invariant under reversal of the sign of $\tau(s)$; thus this formula is consistent with (3), which only gives us $\vert \tau(s) \vert$. Indeed, the sign of $\tau$ cannot be determined from (1)-(3); the derivation of the formula (13) for $\kappa(s)$, is independent of the sign of $\tau(s)$. End of Note.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.